KARAKTERISTIK ORGANOLEPTIK BERAS ANALOG ‘MOSINGGAJA’ DARI MOCAF (Modified Cassava Flour) SINGKONG GAJAH (Manihot utilissima) DAN TEPUNG JAGUNG MANIS - Siti Masithah Fiqtinovri (Universitas Tanjungpura, 2019)
Diversification of food at this time has been done a lot, one of them through making artificial rice or analog rice to reduce the level of rice consumption which is getting higher along with increasing population. Analog rice can use composite materials in the process, such as mocaf of Singkong Gajah and sweet corn flour. The aim of this research is to find an analog rice formulation of mocaf of Singkong Gajah and sweet corn flour (Mosinggaja) which panelists liked and accepted through organoleptic testing. The making of Mosinggaja analog rice is carried out by the cold extrusion method and using a Completely Randomized Design (CRD) with a formulation of 60 g mocaf : 40 g corn flour ; 70 g mocaf : 30 g corn flour ; 80 g of mocaf : 20 g of corn flour. Based on organoleptic test results, Mosinggaja analog rice grain that is accepted by panelist was the formulation of 80 g of mocaf : 20 g of corn flour with a value of 4.12 (like), and the description of rice grain were white color (3.56), the aroma did not match the type of flour (2.60), rather fragile texture (3.16), and non-uniform uniformity of rice grains (2.64). While the Mosinggaja analog rice formulation that received by the panelists was a formulation of 80 g of mocaf : 40 g of corn flour with a value of 3.12 (rather like) and the description of rice were slightly yellowish-white color (3.20), the distinctive aroma of flour (2, 76), slightly sticky texture between rice granules (3.44), and rather sweet taste (3.04).